VALIDITAS LEMBAR KERJA PESERTA DIDIK INKUIRI TERBIMBING PADA MATERI SISTEM EKSKRESI MANUSIA - Zuni Mitasari; Apliana Lamboya; Hasminar Rachman Fidiastuti (Universitas Tribhuwana Tunggadewi, 2023)
This research aims to determine the validity of the guided inquiry-based student worksheet on human excretory system material at junior high school level. This type of this research, namely development research using the modified ADDIE model. The research was conducted at SMP Negeri 16 Malang. Â The data collection instruments include (1) LKPD validation questionnaire, which consists of material expert and media expert validation questionnaires, (2) user expert questionnaires, in this case teachers, and (3) student response questionnaires. Based on the assessment of material experts, they obtained a score of 80.9% (valid), media experts scored 96.3% (valid), teacher user experts scored 83.5% (valid), and small-scale student response scores were 70% (good), and large scale 68% (Good). The inquiry LKPD product is valid and can be continued with quasi-experiments to determine the effect of using the product on the results and learning process.